Distinctive barriers to antiretroviral therapy adherence among non-adherent adolescents living with HIV in Botswana. Issue 2 (1st February 2018) - Yang, Elizabeth; Mphele, Seipone; Moshashane, Neo; Bula, Boineelo; Chapman, Jennifer; Okatch, Harriet; Pettitt, Ed; Tshume, Ontibile; Marukutira, Tafireyi; Anabwani, Gabriel; Lowenthal, Elizabeth
ABSTRACT: Levels of adherence to HIV treatment are lower among adolescents compared with older and younger individuals receiving similar therapies. We purposely sampled the most and least adherent adolescents from a 300-adolescent longitudinal HIV treatment adherence study in Gaborone, Botswana. Multiple objective and subjective measures of adherence were available and study participants were selected based on sustained patterns of either excellent or poor adherence over a one-year period. Focus group discussions (FGD) and in-depth interviews (IDI) were conducted with the adolescents and a subset of their caregivers with the goal of revealing barriers and facilitators of adherence. Focus groups were segregated by adherence classification of the participants. Following coding of transcripts, matrices were developed based on participants' adherence classifications in order to clarify differences in themes generated by individuals with different adherence characteristics. 47 adolescents and 25 adults were included. The non-adherent adolescents were older than the adherent adolescents (median age 18 years (IQR 16–19) vs. 14 years (IQR 12–15 years)), with median time on treatment near 10 years in both groups. Interference with daily activities, concerns about stigma and discrimination, side effects, denial of HIV status, and food insecurity arose as challenges to adherence among both those who were consistently adherent and those who were poorly-adherent to their medications. Low outcome expectancy, treatment fatigue, mental health and substance use problems, and mismatches between desired and received social support were discussed only among poorly adherent adolescents and their caregivers. Challenges raised only among adolescents and caregivers in the non-adherent groups are hypothesis-generating, identifying areas that may have a greater contribution to poor outcomes than challenges faced by both adherent and non-adherent adolescents. The contribution of these factors to poor outcomes should be explored in future studies.